2015
DOI: 10.1080/21646821.2015.1073069
|View full text |Cite
|
Sign up to set email alerts
|

Bulbar and Limb Myorhythmia with “Smooch Sign”: A Distinctive Movement Disorder in an Adult Patient with Reversible Anti-NMDA Receptor Encephalitis Associated with an Ovarian Teratoma

Abstract: Anti-N-Methyl-D-Aspartate receptor encephalitis is a recently described entity (Dalmau et al. 2007, 2008) that may present with a variety of complex movements in addition to other features (Kleinig et al. 2008). The purpose of our presentation of such a patient is twofold: (1) to characterize these complex oculo-oro-linguo-masticatory and limb movements with "smooch sign" as myorhythmia, based on a combined clinical and electrophysiological analysis (Masucci et al. 1984); and (2) to document possibly character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…( Florance et al, 2009 ; Mohammad et al, 2014 ) Ferioli et al( Ferioli et al, 2010 ) reported a case of paraneoplastic anti-NMDAR encephalitis with prominent jaw-opening dystonia and paroxysmal opisthotonos. Neiman et al( Neiman et al, 2015 ) described a case of anti-NMDAR encephalitis with prominent bulbar and limb myorhythmia with "Smooch Sign". Duan et al( Duan et al, 2016 ) mentioned that in patients aged more than 18 years, choreoathetoid movements are rarely seen in opposed to the age group below 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…( Florance et al, 2009 ; Mohammad et al, 2014 ) Ferioli et al( Ferioli et al, 2010 ) reported a case of paraneoplastic anti-NMDAR encephalitis with prominent jaw-opening dystonia and paroxysmal opisthotonos. Neiman et al( Neiman et al, 2015 ) described a case of anti-NMDAR encephalitis with prominent bulbar and limb myorhythmia with "Smooch Sign". Duan et al( Duan et al, 2016 ) mentioned that in patients aged more than 18 years, choreoathetoid movements are rarely seen in opposed to the age group below 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of myorhythmia is brainstem 3 and thalamic strokes, but it can also be found in patients with autoimmune 4 , 5 and demyelinating disorders, drug or toxin intake, trauma, Listeria rhombencephalitis 6 and Whipple disease where it commonly manifests with oculomasticatory rather than limb myorhythmia. 7 Case reports have also described myorhythmia associated with COVID-19 Acute Hemorrhagic Necrotizing Encephalopathy, 8 brain tumors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been frequently reported as oculo-masticatory myorhythmia in the context of Whipple's disease, caused by the infection of the central nervous system by Trophyrema whipplei ( 140 ). Other conditions where myorhythmia has been reported are stroke ( 139 ), anti-NMDA encephalitis ( 141 , 142 ), anti-IgLON5 disease ( 143 ), interferon alpha-2a use ( 144 ), Hashimoto encephalopathy ( 145 ), and X-linked dystonia-parkinsonism ( 146 ). As myorhythmia is often associated with conditions that are potentially treatable, it is important to be familiar with this phenomenology and its differential diagnoses.…”
Section: Tremor In the Setting Additional Neurological Featuresmentioning
confidence: 99%